'Double-muscling' and pelvic tilt phenomena in rabbits with the cystine-knot motif deficiency of myostatin on exon 3. Issue 5 (21st May 2019) - Zhang, Ting; Lu, Yaoyao; Song, Shaozheng; Lu, Rui; Zhou, Minya; He, Zhengyi; Yuan, Tingting; Yan, Kunning; Cheng, Yong
Abstract : Gene mutations at different gene sites will produce totally different phenotypes or biological functions in gene-edited animals. An allelic series of mutations in the myostatin ( MSTN ) gene can cause the 'double-muscling' phenotype. Although there have been many studies performed on MSTN -mutant animals, there have been few studies that have investigated the cystine-knot motif in exon 3 of MSTN in rabbits. In the current study, CRISPR/Cas9 sgRNA anchored exon 3 of a rabbit's MSTN was used to disrupt the cystine-knot motif to change the MSTN construction and cause a loss of its function. Eleven MSTN -KO founder rabbits were generated, and all of them contained biallelic modifications. Various mutational MSTN amino acid sequences of the 11 founder rabbits were modeled to the tertiary structure using the SWISS-MODEL, and the results showed that the structure of the cystine-knot motif of each protein in the founder rabbits differed from the wild-type (WT). The MSTN -KO rabbits displayed an obvious 'double-muscling' phenomena, with a 20−30% increase in body weight compared with WT rabbits. In the MSTN -KO rabbits, all of the MSTN −/− rabbits showed teeth dislocation and tongue enlargement, and the percentage of rabbits having pelvic tilt was 0% in MSTN +/+, 0% in MSTN +/−, 77.78% in female MSTN −/− rabbits, and 37.50% in male MSTN −/− rabbits. The biomechanical mechanism of pelvic tilt and teeth dislocation in the MSTN -KO rabbits requires further investigation. These newly generated MSTN -KO rabbits will serve as an important animal model, not only for studying skeletal muscle development, but also for biomedical studies in pelvic tilt correction and craniofacial research.